Composite EVA material, adhesive film and preparation method, application and battery assembly thereof

By grafting nano ZnO:Eu3+ in EVA materials, the composite EVA materials are prepared, which solves the problem that photovoltaic films cannot utilize ultraviolet light, improves the photoelectric conversion efficiency and maintains the visible light transmittance, and significantly improves the photoelectric conversion of solar cells performance.

CN116333642BActive Publication Date: 2025-01-10SHANGHAI LANGYI FUNCTIONAL MATERIALS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211741238.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-01-10
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

The existing photovoltaic adhesive films cannot effectively utilize ultraviolet light, resulting in low photoelectric conversion efficiency of solar cells. The added inorganic photoelectric conversion materials will reduce visible light transmission and cannot effectively improve photoelectric conversion efficiency.

Method used

The composite EVA material, including the EVA matrix and nano ZnO:Eu3+ grafted on the EVA matrix, and free nano ZnO:Eu3+, were prepared by specific hydrolysis reactions and grafting methods, and the content of total nano ZnO:Eu3+ is controlled to be low. at 4.5%, to improve the photoelectric conversion efficiency.

Benefits of technology

The visible light transmittance of the composite EVA packaging film is maintained at more than 90%, and the photoelectric conversion efficiency is increased to more than 13.2%, which is far beyond the efficiency of the pure EVA packaging film and does not affect the transparency of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116333642B_ABST
    Figure CN116333642B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite EVA material, an adhesive film, a preparation method thereof, an application thereof, and a battery assembly. The composite EVA material of the present invention comprises an EVA matrix, nano ZnO:Eu grafted on the CO of the EVA matrix, 3+ and free nano ZnO:Eu 3+ ; Total nano ZnO:Eu 3+ The mass percentage of the EVA matrix is ​​not higher than 4.5%, and the total nano ZnO:Eu 3+ Nano ZnO:Eu grafted on the EVA substrate 3+ and the free nano ZnO:Eu 3+ The composite EVA packaging film made from the composite EVA material of the present invention has no significant reduction in visible light transmittance and effectively improves the photoelectric conversion efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite EVA material, an adhesive film, a preparation method, an application and a battery assembly thereof. Background Art

[0002] When producing solar cells, photovoltaic films are needed to encapsulate the cells in order to improve the performance and life of solar cell modules. Photovoltaic resin has the characteristics of high light transmittance, UV resistance, and resistance to yellowing due to humidity and heat. It is the most widely used photovoltaic film material in commercial scenarios of solar cells. Its performance directly determines the product quality and service life of photovoltaic modules. Although photovoltaic resin has the characteristics of high light transmittance, the resin film has a blocking effect on ultraviolet rays, so that ultraviolet light, which accounts for 5% of the energy in sunlight, cannot be used by the cells and then undergo photoelectric conversion, resulting in low photoelectric conversion efficiency.

[0003] Photoconversion materials can convert ultraviolet light into visible light that can be used by solar cells, thereby broadening the spectral response range of solar cells and improving the photoelectric conversion efficiency of solar cells. In the prior art, photoconversion materials mainly include organic photoconversion materials and inorganic photoconversion materials. Among them, organic photoconversion materials have the problem of poor light stability, which greatly limits their promotion and application; inorganic photoconversion materials have better light stability. Based on the Rayleigh scattering formula, reducing the particle size to nanometer size can greatly reduce scattering losses without affecting the transparency of the resin film. Although the addition of inorganic photoconversion material particles can convert ultraviolet light into usable visible light, it will also cause the visible light transmittance of the resin film to decrease, resulting in the overall photoelectric conversion efficiency cannot be effectively improved.

[0004] Therefore, there is an urgent need for an encapsulation film that can improve the photoelectric conversion efficiency of the resin film. Summary of the invention

[0005] The technical problem solved by the present invention is to overcome the defects of the prior art resin adhesive film that cannot utilize ultraviolet light and has low photoelectric conversion efficiency, and the added inorganic photoelectric conversion material will reduce the visible light transmittance and the photoelectric conversion efficiency cannot be effectively improved, and provide a composite EVA material, adhesive film and its preparation method, application, and battery assembly. The encapsulation adhesive film made of the composite EVA material of the present invention effectively improves the photoelectric conversion efficiency.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention provides a composite EVA material, which comprises an EVA matrix, nano ZnO:Eu grafted on -CO- of the EVA matrix, 3+ and free nano ZnO:Eu 3+ ; Total nano ZnO:Eu 3+The mass percentage of the EVA matrix is ​​not higher than 4.5%, and the total nano ZnO:Eu 3+ Nano ZnO:Eu grafted on the EVA substrate 3+ and the free nano ZnO:Eu 3+ composition.

[0008] In the present invention, the EVA may be the EVA conventionally used in the field of photovoltaic encapsulation films. Preferably, the vinyl acetate content in the EVA is 20-28%, more preferably 28%; the vinyl acetate content refers to the mass percentage of vinyl acetate in the EVA.

[0009] In some preferred embodiments of the present invention, the EVA is UE2825 produced by Sulbond Chemical.

[0010] In the present invention, those skilled in the art can understand that ZnO:Eu 3+ The structural formula of the compound formed by grafting onto the -CO- of the EVA is shown in the following formula (1):

[0011]

[0012] Wherein, x1, x2, y1 and y2 are all positive integers.

[0013] It is generally understood by those skilled in the art that the nano ZnO:Eu 3+ It is a conventional inorganic light conversion material in the art, also known as europium-doped nano zinc oxide.

[0014] In the present invention, those skilled in the art can understand that the free nano ZnO:Eu 3+ Refers to the nano ZnO:Eu that is not grafted to the EVA 3+ .

[0015] In the present invention, the total nano ZnO:Eu 3+ The europium doping ratio is preferably 4-10%, more preferably 5-8%, for example 5.56%, 6.10%, 6.35%, 6.42%, 7.14% or 7.67%; more preferably 7-8%; wherein the europium doping ratio refers to the mass ratio of europium oxide to zinc oxide.

[0016] In the present invention, the total nano ZnO:Eu 3+ The mass percentage of the EVA is preferably 0.2-4%, more preferably 0.5-3.5%, and further preferably 0.53%, 1.06%, 1.61%, 2.10% or 3.50%.

[0017] In the present invention, those skilled in the art can understand that the EVA matrix may include a portion of the EVA matrix that is not covered with nano ZnO:Eu 3+ Grafted EVA.

[0018] The present invention also provides a method for preparing a composite EVA material, which comprises the following steps:

[0019] S1: The mixed solution containing zinc source and europium source is hydrolyzed to obtain nano ZnO:Eu 3+ Precursor; the temperature of the hydrolysis reaction is not less than 160°C, and the time of the hydrolysis reaction is not less than 16 hours; the hydrolysis reaction is carried out at a pH of 7 to 10;

[0020] S2: the nano ZnO:Eu 3+ The precursor and the EVA as described above are subjected to grafting reaction and then dried; the nano ZnO:Eu 3+ After the precursor loses bound water, the total nano ZnO:Eu as described above is obtained. 3+ .

[0021] In S1, the zinc source can be a conventional zinc source in the art that can provide Zn 2+ The compound is preferably a zinc salt, more preferably one or more of zinc nitrate, zinc sulfate and zinc carbonate, and further more preferably zinc nitrate.

[0022] In S1, the europium source can be a conventional source in the art that can provide Eu 3+ The compound is preferably a europium salt, more preferably one or more of europium nitrate, europium sulfate and europium carbonate, and further more preferably europium nitrate.

[0023] In S1, preferably, the mixed solution also includes an anionic surfactant.

[0024] The hydrophile-lipophile balance (HLB) of the anionic surfactant is preferably 10-15, more preferably 10-12, and even more preferably 10.638.

[0025] Wherein, the anionic surfactant is preferably sodium dodecylbenzene sulfonate.

[0026] The mass of the anionic surfactant may be conventional in the art, preferably accounting for 1-6% of the total mass of the zinc source and the europium source, more preferably 5-6%, and further more preferably 5.60%, 5.65% or 5.66%.

[0027] In S1, preferably, the mixed solution is preheated before the hydrolysis reaction.

[0028] Preferably, the preheating temperature is 80-110°C, more preferably 90°C.

[0029] Preferably, the preheating time is 1 to 4 hours, more preferably 2 hours.

[0030] In S1, preferably, the hydrolysis reaction is carried out at a pH of 8.5 to 10, more preferably at a pH of 8.5, 9.0, 9.5 or 10.

[0031] The pH is generally adjusted using a pH adjuster.

[0032] The pH adjuster is preferably an alkaline compound free of metal cations, more preferably ammonia water and / or urea, and even more preferably ammonia water.

[0033] The amount of the pH adjuster used is preferably such that the pH of the mixed solution meets the above-mentioned limitation.

[0034] The pH adjuster may be added in a conventional manner in the art, preferably dropwise.

[0035] In S1, the zinc-europium oxide precursor refers to the precursor that can form nano ZnO:Eu after losing bound water. 3+ The substance can generally be zinc europium hydroxide.

[0036] In S1, the temperature of the hydrolysis reaction is preferably 180-220°C, more preferably 180°C, 200°C or 220°C.

[0037] In S1, the hydrolysis reaction time is preferably 16 to 30 hours, more preferably 20 to 30 hours, such as 20 hours, 24 hours or 30 hours.

[0038] In S1, preferably, the molar ratio of the zinc source and the europium source is according to the above-mentioned ZnO:Eu 3+ The europium doping ratio is determined as described in .

[0039] In S2, preferably, the EVA is first dissolved in an organic solvent to form an EVA solution, and then mixed with the nano ZnO:Eu 3+ The precursor undergoes the reaction.

[0040] The organic solvent may be a conventional solvent in the art that can dissolve the EVA, preferably toluene.

[0041] The concentration of the EVA solution may be conventional in the art, preferably 5 to 15 g / mL, more preferably 10 g / mL.

[0042] In S2, the temperature of the grafting reaction is higher than the melting point of the EVA and lower than the boiling point of the organic solvent in the S2 system.

[0043] Preferably, the temperature of the grafting reaction is 80-110°C, more preferably 90°C.

[0044] The grafting reaction time may be conventional in the art, preferably 1.5 to 3 hours, more preferably 2 hours.

[0045] In S2, the drying can be performed by conventional methods in the art, preferably vacuum drying.

[0046] It is generally understood by those skilled in the art that the purpose of the drying is to remove the nano ZnO:Eu 3+ The bound water in the precursor converts it into nano zinc europium oxide.

[0047] In S2, those skilled in the art can understand that the nano ZnO:Eu 3+ The precursor and the EVA undergo a grafting reaction. Not all zinc oxide europium precursors can be grafted onto the EVA, but some zinc oxide europium precursors can be grafted onto the EVA. After drying and removing bound water, nano ZnO:Eu grafted onto the EVA is formed. 3+ The remaining zinc oxide europium precursor is dried to remove bound water to form the free nano ZnO:Eu 3+ .

[0048] In S2, after the grafting reaction and before the drying, an extraction step is preferably further included, wherein the extraction is used to separate inorganic salt ions in the mixed solution obtained after the grafting reaction.

[0049] When the system contains inorganic salt ions such as nitrate ions or sodium ions, the obtained composite glue does not have the photoconversion function. The extraction step of the present invention is used to separate the inorganic salt ions.

[0050] The solvent used for the extraction can be any conventional solvent in the art, preferably one or more of toluene, carbon tetrachloride, chloroform and dichloromethane.

[0051] The organic phase obtained after the extraction is a mixed solution C, and the mixed solution C is dried to obtain a composite EVA material with a light conversion function.

[0052] The drying is preferably vacuum drying.

[0053] The present invention also provides a composite EVA material prepared by the preparation method as described above.

[0054] The present invention also provides a composite EVA packaging film, which is obtained by molding the composite EVA material as described above.

[0055] In the present invention, the molding can be performed by conventional methods in the art, and preferably the composite EVA material is kneaded and stretched to form.

[0056] The kneading temperature may be conventional in the art, preferably 90-120°C, such as 100°C.

[0057] The stretching temperature may be conventional in the art, preferably 120-160°C, more preferably 130-150°C, such as 140°C.

[0058] In the present invention, preferably, the composite EVA material is crushed into particles before the molding.

[0059] The present invention also provides an application of the composite EVA material or the composite EVA packaging film in a photovoltaic module.

[0060] The present invention also provides a battery cell comprising the composite EVA packaging film.

[0061] The present invention also provides a photovoltaic module comprising the above-mentioned solar cell.

[0062] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0063] The reagents and raw materials used in the present invention are commercially available.

[0064] The positive improvement effect of the present invention is that the visible light transmittance of the composite EVA encapsulation film of the present invention is equivalent to that of the pure EVA film, both of which are above 90%, and even as high as 92-93%; the photoelectric conversion efficiency reaches above 13.2%, and even reaches above 14%, which can be increased by more than 1 percentage point compared with the photoelectric conversion efficiency of the pure EVA encapsulation film. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 This is a TEM image of the composite EVA packaging film obtained in Example 1;

[0066] Figure 2 This is the infrared spectrum of the pure EVA packaging film obtained in Comparative Example 1;

[0067] Figure 3 This is the infrared spectrum of the composite EVA packaging film obtained in Example 1. DETAILED DESCRIPTION

[0068] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0069] The main raw material information used in the following examples and comparative examples is as follows:

[0070] EVA: Sailbon Chemical EVA2825, with 28% vinyl acetate (VA) content;

[0071] POE: Dow Chemical POE8658;

[0072] Zinc nitrate, europium nitrate, sodium dodecylbenzene sulfonate, urea, and toluene were purchased from Aladdin, all of analytical grade;

[0073] Ammonia water (analytical grade, NH3 concentration 25%, purchased from Aladdin).

[0074] The europium doping ratio in the following embodiments and comparative examples = (m1*176 / 446) / (m2*81 / 189)﹡100%, wherein m1 is the mass of Eu(NO3)3·6H2O, m1*176 / 446 is the mass of Eu2O3 formed by complete hydrolysis of Eu(NO3)3·6H2O, m2 is the mass of anhydrous zinc nitrate, and m2*81 / 189 is the mass of ZnO formed by complete hydrolysis of anhydrous zinc nitrate; the ratio of dry mass of precursor to mass of EVA = (m1*176 / 446+m2*81 / 189) / m3﹡100%, wherein m3 is the mass of EVA, and the dry mass of the precursor is the sum of the masses of Eu2O3 and ZnO.

[0075] Among them, zinc nitrate and europium nitrate can be basically completely hydrolyzed under a sufficiently long hydrolysis time of the present invention, so the mass of the generated ZnO and Eu2O3 is accurately converted according to the mass of the raw materials zinc nitrate and europium nitrate.

[0076] Example 1

[0077] First, 0.116 g of anhydrous zinc nitrate, 0.008 g of europium nitrate (Eu(NO3)3·6H2O) (europium doping ratio of 6.35%), and 0.007 g of sodium dodecylbenzene sulfonate were added to 100 mL of deionized water, placed in a hydrothermal reactor, heated to 90°C, and kept at 90°C for 2 hours to obtain a mixed solution A. Then, the temperature of the mixed solution A was raised to 180°C, urea was added dropwise until the pH was 8.5, and the reaction was continued for 24 hours to obtain a mixture containing nano ZnO:Eu 3+Precursor mixed solution B. Finally, 10g EVA (the mass ratio of the precursor to EVA is 0.53%) was heated and dissolved in 100mL toluene solution, added to the mixed solution B, mixed and reacted at 90°C for 2h, and the upper solution was extracted with toluene to obtain a mixed solution C. The mixed solution C was vacuum dried, the toluene solvent was evaporated, and a composite EVA block material with a light conversion function was obtained after precipitation. The block material was broken into particles, kneaded in a HAAKE Mixer 600 rheometer set at 100°C for 10min, and then stretched at 140°C to form a film to obtain a composite EVA encapsulation film.

[0078] Example 2

[0079] First, 0.232g of anhydrous zinc nitrate, 0.016g of europium nitrate (Eu(NO3)3·6H2O) (europium doping ratio of 6.35%), and 0.013g of sodium dodecylbenzene sulfonate were added to 100mL of deionized water, placed in a hydrothermal reactor, heated to 90°C, and kept at 90°C for 2h to obtain a mixed solution A. Then, the temperature of the mixed solution A was raised to 180°C, and ammonia water was added dropwise to a pH of 9.0 and the reaction was continued for 24h to obtain a mixture containing nano ZnO:Eu 3+ Precursor mixed solution B. Finally, 10g EVA (the mass ratio of the precursor to EVA is 1.06%) was heated and dissolved in 100mL toluene solution, added to the mixed solution B, mixed at 90°C for 2h, and the upper solution was extracted with toluene to obtain a mixed solution C. The mixed solution C was vacuum dried to evaporate the toluene solvent, and a composite EVA block material with a light conversion function was obtained after precipitation. The block material was broken into particles, kneaded in a HAAKE Mixer600 rheometer set at 100°C for 10min, and then stretched at 140°C to form a film to obtain a composite EVA encapsulation film.

[0080] Example 3

[0081] First, 0.348g of anhydrous zinc nitrate, 0.029g of europium nitrate (Eu(NO3)3·6H2O) (europium doping ratio of 7.67%), and 0.021g of sodium dodecylbenzene sulfonate were added to 100mL of deionized water, placed in a hydrothermal reactor, heated to 90°C, and kept at 90°C for 2h to obtain a mixed solution A. Then, the temperature of the mixed solution A was raised to 180°C, and ammonia water was added dropwise to a pH of 9.0 and the reaction was continued for 24h to obtain a mixture containing nano ZnO:Eu 3+Precursor mixed solution B. Finally, 10g EVA (the mass ratio of the precursor to EVA is 1.58%) was heated and dissolved in 100mL toluene solution, added to the mixed solution B, mixed at 90°C for 2h, and the upper solution was extracted with toluene to obtain a mixed solution C. The mixed solution C was vacuum dried to obtain a composite EVA block material with a light conversion function after precipitation. The block material was broken into particles, kneaded in a HAAKE Mixer600 rheometer set at 100°C for 10min, and then stretched at 140°C to form a film to obtain a composite EVA encapsulation film.

[0082] Example 4

[0083] First, 0.464 g of anhydrous zinc nitrate, 0.028 g of europium nitrate (Eu(NO3)3·6H2O) (europium doping ratio of 5.56%), and 0.029 g of sodium dodecylbenzene sulfonate were added to 100 mL of deionized water, placed in a hydrothermal reactor, heated to 90°C, and kept at 90°C for 2 hours to obtain a mixed solution A. Then, the temperature of the mixed solution A was raised to 180°C, and ammonia water was added dropwise to a pH of 9.5 and the reaction was continued for 24 hours to obtain a mixture containing nano ZnO:Eu 3+ Precursor mixed solution B. Finally, 10g EVA (the mass ratio of the precursor to EVA is 2.11%) was heated and dissolved in 100mL toluene solution, added to the mixed solution B, mixed at 90°C for 2h, and the upper solution was extracted with toluene to obtain a mixed solution C. The mixed solution C was vacuum dried to evaporate the toluene solvent, and a composite EVA block material with a light conversion function was obtained after precipitation. The block material was broken into particles, kneaded in a HAAKE Mixer 600 rheometer set at 100°C for 10min, and then stretched at 140°C to form a film to obtain a composite EVA encapsulation film.

[0084] Example 5

[0085] First, 0.116 g of anhydrous zinc nitrate, 0.008 g of europium nitrate (Eu(NO3)3·6H2O) (europium doping ratio of 6.35%), and 0.007 g of sodium dodecylbenzene sulfonate were added to 100 mL of deionized water, placed in a hydrothermal reactor, heated to 90°C, and kept at 90°C for 2 hours to obtain a mixed solution A. Then, the temperature of the mixed solution A was raised to 200°C, and ammonia water was added dropwise to a pH of 8.5 and the reaction was continued for 20 hours to obtain a nano ZnO:Eu 3+Precursor mixed solution B. Finally, 10g EVA (the mass ratio of the precursor to EVA is 0.53%) was heated and dissolved in 100mL toluene solution, added to the mixed solution B, mixed at 90°C for 2h, and the upper solution was taken to obtain a mixed solution C. The mixed solution C was vacuum dried to evaporate the toluene solvent, and a composite EVA block material with a light conversion function was obtained after precipitation. The block material was broken into particles, kneaded in a HAAKEMixer 600 rheometer set at 100°C for 10min, and then stretched at 140°C to form a film, thereby obtaining a composite EVA encapsulation film.

[0086] Example 6

[0087] First, 0.116 g of anhydrous zinc nitrate, 0.009 g of europium nitrate (Eu(NO3)3·6H2O) (europium doping ratio of 7.14%), and 0.007 g of sodium dodecylbenzene sulfonate were added to 100 mL of deionized water, placed in a hydrothermal reactor, heated to 90°C, and kept at 90°C for 2 hours to obtain a mixed solution A. Then, the temperature of the mixed solution A was raised to 220°C, and ammonia water was added dropwise to a pH of 9.0 and the reaction was continued for 30 hours to obtain a mixture containing nano ZnO:Eu 3+ Mixed solution B of the precursor. Finally, 10g of EVA (the mass ratio of the dry mass of the precursor to the mass of EVA is 0.53%) was heated and dissolved in 100mL of toluene solution, added to the mixed solution B, mixed at 90°C for 2h, and the upper layer of the solution was taken to obtain a mixed solution C. The mixed solution C was dried under vacuum to evaporate the solvent, and a composite EVA block material with a light conversion function was obtained after precipitation. The block material was broken into particles, kneaded in a HAAKEMixer 600 rheometer set at 100°C for 10min, and then stretched at 140°C to form a film, thereby obtaining a composite EVA encapsulation film.

[0088] Example 7

[0089] First, 0.232g of anhydrous zinc nitrate, 0.016g of europium nitrate (Eu(NO3)3·6H2O) (europium doping ratio of 6.35%), and 0.014g of sodium dodecylbenzene sulfonate were added to 100mL of deionized water, placed in a hydrothermal reactor, heated to 90°C, and kept at 90°C for 2h to obtain a mixed solution A. Then, the temperature of the mixed solution A was raised to 180°C, and ammonia water was added dropwise to a pH of 9.0 and the reaction was continued for 24h to obtain a mixture containing nano ZnO:Eu 3+Precursor mixed solution B. Finally, 10g EVA (the mass ratio of the precursor to EVA is 1.06%) was heated and dissolved in 100mL toluene solution, added to the mixed solution B, mixed at 90°C for 2h, and the upper solution was extracted with toluene to obtain a mixed solution C. The mixed solution C was vacuum dried to evaporate the toluene solvent, and a composite EVA block material containing a light conversion function was obtained after precipitation. The block material was broken into particles, kneaded in a HAAKE Mixer 600 rheometer set at 100°C for 10min, and then stretched at 140°C to form a film to obtain a composite EVA encapsulation film.

[0090] Example 8

[0091] First, 0.77g of anhydrous zinc nitrate, 0.051g of europium nitrate (Eu(NO3)3·6H2O) (europium doping ratio of 6.10%), and 0.042g of sodium dodecylbenzene sulfonate were added to 100mL of deionized water, placed in a hydrothermal reactor, heated to 90°C, and kept at 90°C for 2h to obtain a mixed solution A. Then, the temperature of the mixed solution A was raised to 180°C, and ammonia water was added dropwise to a pH of 9.0 and the reaction was continued for 24h to obtain a mixture containing nano ZnO:Eu 3+ Precursor mixed solution B. Finally, 10g EVA (the mass ratio of the precursor to EVA is 3.5%) was heated and dissolved in 100mL toluene solution, added to the mixed solution B, mixed at 90°C for 2h, and the upper solution was extracted with toluene to obtain a mixed solution C. The mixed solution C was vacuum dried to evaporate the toluene solvent, and a composite EVA block material with a light conversion function was obtained after precipitation. The block material was broken into particles, kneaded in a HAAKE Mixer 600 rheometer set at 100°C for 10min, and then stretched at 140°C to form a film to obtain a composite EVA encapsulation film.

[0092] Example 9

[0093] First, 0.043g of anhydrous zinc nitrate, 0.003g of europium nitrate (Eu(NO3)3·6H2O) (europium doping ratio of 6.35%), and 0.0026g of sodium dodecylbenzene sulfonate were added to 100mL of deionized water, placed in a hydrothermal reactor, heated to 90°C, and kept at 90°C for 2h to obtain a mixed solution A. Then, the temperature of the mixed solution A was raised to 180°C, urea was added dropwise until pH = 8.5, and the reaction was continued for 24h to obtain a mixture containing nano ZnO:Eu 3+Precursor mixed solution B. Finally, 10g EVA (the mass ratio of the precursor to EVA is 0.2%) was heated and dissolved in 100mL toluene solution, added to the mixed solution B, mixed and reacted at 90°C for 2h, and the upper solution was extracted with toluene to obtain a mixed solution C. The mixed solution C was vacuum dried, the toluene solvent was evaporated, and a composite EVA block material with a light conversion function was obtained after precipitation. The block material was broken into particles, kneaded in a HAAKE Mixer600 rheometer set at 100°C for 10min, and then stretched at 140°C to form a film to obtain a composite EVA encapsulation film.

[0094] Comparative Example 1

[0095] The EVA was crushed into particles, kneaded in a HAAKE Mixer 600 rheometer set at 100° C. for 10 min, and then stretched at 140° C. to form a film to obtain an EVA encapsulating film.

[0096] Comparative Example 2

[0097] First, 0.116g of anhydrous zinc nitrate, 0.008g of europium nitrate (Eu(NO3)3·6H2O), and 0.007g of sodium dodecylbenzene sulfonate were added to 100mL of deionized water, heated to 90°C, placed in a hydrothermal reactor, and kept at 90°C for 2h to obtain a mixed solution A. Then, the temperature of the mixed solution A was raised to 180°C, 0.002g of urea was added dropwise, and the reaction continued for 24h to obtain a mixed solution B. The mixed solution B was centrifuged and dried to obtain a light conversion powder D, and the powder D and 10g of crushed EVA particles were kneaded in a HAAKE Mixer 600 rheometer set at 100°C for 10min, and then stretched at 140°C to form a film.

[0098] Comparative Example 3

[0099] First, 0.348g of anhydrous zinc nitrate, 0.023g of europium nitrate (Eu(NO3)3·6H2O), 0.021g of sodium dodecylbenzene sulfonate, and 0.006g of urea were added to 100mL of deionized water, and reacted for 3h at a water bath temperature of 90°C to obtain a precursor, which was aged for 2h and then vacuum filtered, washed with distilled water several times, and then washed with anhydrous ethanol 3 times. The obtained product was placed in a drying oven and dried at 100°C for 2h. The collected precursor product was calcined at 450°C in a muffle furnace for 2h to finally obtain nano zinc oxide europium powder. The nano zinc oxide europium powder was kneaded with 10g of EVA in a HAAKE Mixer 600 rheometer set at 100°C for 10min, and then stretched at 140°C to form a film.

[0100] Comparative Example 4

[0101] 10 g of EVA was replaced with 10 g of POE, which was heated and dissolved in 100 mL of toluene solution, and added to the mixed solution B. The other steps and conditions were the same as those in Example 1 to obtain a composite POE material and a composite POE encapsulation film.

[0102] Comparative Example 5

[0103] First, 0.214g of ethyl orthosilicate and 0.007g of bismuth nitrate (Bi(NO3)3·5H2O) were dissolved in 100mL of deionized water, stirred thoroughly to form a transparent solution, placed in a hydrothermal reactor, and the pH value of the above solution was adjusted to 9.0 with ammonia water. The mixture was kept at 90°C for 2h to obtain a mixed solution A. Then, the temperature of the above mixed solution A was raised to 180°C and reacted for 24h to obtain a mixed solution B. Finally, 10g of EVA was heated and dissolved in 100mL of toluene solution, added to the mixed solution B, mixed at 90°C for 2h, and the upper solution was extracted to obtain a mixed solution C. The mixed solution C was vacuum dried to obtain an EVA bulk material containing a photoconversion material after precipitation. The bulk material was broken into particles, kneaded in a HAAKE Mixer 600 rheometer set at 100°C for 10min, and then stretched at 140°C to form a film.

[0104] Comparative Example 6

[0105] Ammonia water was added dropwise to the mixed solution A until the pH value reached 11. Other conditions and steps were the same as those in Example 2 to obtain a composite EVA material and a composite EVA encapsulation film.

[0106] Comparative Example 7

[0107] 0.05 g of europium nitrate (Eu(NO3)3·6H2O) (the europium doping ratio is 19.84%) was added, and the other steps and conditions were the same as those in Example 2 to obtain a composite EVA material and a composite EVA packaging film.

[0108] Comparative Example 8

[0109] The temperature of the mixed solution A was raised to 120° C., and urea was added dropwise. The other steps and conditions were the same as those in Example 1, to obtain a composite EVA material and a composite EVA encapsulation film.

[0110] Comparative Example 9

[0111] The hydrolysis reaction time after the addition of urea was 8 h, and the other conditions were the same as those in Example 1, to obtain a composite EVA material and a composite EVA encapsulation film.

[0112] Comparative Example 10

[0113] The amount of EVA added was 1 g, the mass ratio of the precursor to EVA was 5.3%, and the rest was the same as in Example 1, to obtain a composite EVA material and a composite EVA encapsulation film.

[0114] Effect Example

[0115] The performance indicators of the encapsulation films obtained in Examples 1 to 9 and Comparative Examples 1 to 10 were measured by the following methods. In order to make the test results comparable, the thickness of the films used for the tests was 0.5 mm.

[0116] 1. TEM characterization

[0117] The composite EVA encapsulation film obtained in Example 1 was characterized by a transmission electron microscope (TEM). Figure 1 As shown. Figure 1 It can be seen that the particle size of zinc-europium oxide particles is about 20nm and is evenly distributed in the EVA substrate.

[0118] 2. FT-IR characterization

[0119] The pure EVA encapsulation film of comparative example 1 and the composite EVA encapsulation film of example 1 were characterized by Fourier infrared spectroscopy, and the spectra were as follows: Figure 2 and Figure 3 As shown. Figure 2 and Figure 3 It can be seen from the comparison that the composite EVA encapsulation film is at 1735cm -1 The absorption peak at is significantly weaker than that of pure EVA encapsulation film. The absorption peak here is the characteristic absorption peak of -C=O, proving that zinc oxide and europium are grafted on the -C=O of EVA.

[0120] 3. Transparency and color test: The relative transmittance in the UV / visible light region is tested using a UV-visible spectrophotometer.

[0121] The basic operation of the device is as follows:

[0122] (1) Before testing, check whether there is anything blocking the light path in the sample chamber.

[0123] (2) Press the "MODE" key to set the test mode to transmittance mode, and the display will show "xxnm x%T".

[0124] (3) Press the wavelength setting key to set the wavelength to 550nm.

[0125] (4) The encapsulation film samples obtained in Examples 1 to 9 and Comparative Examples 1 to 10 were fixed on the optical path using the clamps provided by the equipment, so that the sample film was perpendicular to the optical path. At this time, the "x%T" displayed on the display was the 550nm visible light transmittance of the tested sample. The results are shown in Table 1.

[0126] 4. Solar cell photoelectric conversion efficiency test: The encapsulation films obtained in Examples 1 to 9 and Comparative Examples 1 to 10 were placed on the surface of a single-crystal silicon solar standard cell (a standard solar cell purchased from Zhongke Micro Energy CME-RC, which is a 2cm*2cm single-crystal silicon photovoltaic cell) (illumination area 110cm 2 ),

[0127] Connect to the electrochemical workstation, with a fixed light source intensity of 100mW / m 2 , measure the volt-ampere characteristic curve (IV curve) of the solar cell, and calculate the photoelectric conversion efficiency according to the following formula. The results are shown in Table 1.

[0128]

[0129] Among them, j p —Photocurrent density (mA·cm -2 );

[0130] j d —Dark current density (mA·cm -2 );

[0131] λ— wavelength of incident monochromatic light (nm);

[0132] P in —Light power density received by the photoelectrode (mW·cm -2 ).

[0133] Table 1 Effect data table of each embodiment and comparative example

[0134] sample 550nm visible light transmittance (%) Photoelectric conversion efficiency (%) Example 1 92.9 14.28 Example 2 92.4 14.35 Example 3 91.5 14.55 Example 4 90.1 14.33 Example 5 93.0 14.30 Example 6 92.1 14.42 Example 7 91.9 13.89 Example 8 90.5 14.14 Example 9 92.9 13.28 Comparative Example 1 93.1 13.11 Comparative Example 2 67.7 9.22 Comparative Example 3 77.5 10.25 Comparative Example 4 86.4 11.75 Comparative Example 5 88.5 12.19 Comparative Example 6 80.9 11.33 Comparative Example 7 79.9 10.20 Comparative Example 8 80.1 11.19 Comparative Example 9 80.5 11.97 Comparative Example 10 80.5 12.97

[0135] The above data show that the visible light transmittance of the composite EVA encapsulation film made of the composite EVA material of the present invention is not significantly lower than that of the pure EVA encapsulation film of Comparative Example 1, and is above 90%, and some preferred embodiments reach 92-93%; the photoelectric conversion efficiency is significantly improved compared with the pure EVA encapsulation film of Comparative Example 1, and is above 13.2%, and most embodiments reach above 14%, and the improvement can reach more than 1 percentage point. The improvement of 1 percentage point in photoelectric conversion efficiency means a reduction of about 10% in the cost of photovoltaic power generation, which is of great significance.

[0136] The europium zinc oxide precursor of comparative example 2 is dried to obtain powdered zinc europium oxide, which is then mixed and kneaded with EVA to obtain a composite EVA encapsulation film whose visible light transmittance is significantly lower than that of the pure EVA encapsulation film, and the final photoelectric conversion efficiency is also worse than that of pure EVA.

[0137] Comparative Example 3 did not perform hydrolysis at the temperature specified in the present invention. Instead, the precursor obtained after mixing was calcined at a higher temperature to obtain zinc oxide europium powder, which was then mixed with EVA and kneaded and formed to obtain a composite EVA encapsulation film, whose visible light transmittance and photoelectric conversion efficiency were significantly worse than those of the pure EVA in Comparative Example 1.

[0138] Comparative Example 4 shows that when EVA is replaced with POE, which can also be used as a photovoltaic module encapsulation film resin, the visible light transmittance and photoelectric conversion efficiency of pure POE encapsulation film are basically the same as those of pure EVA encapsulation film. However, the photoelectric conversion efficiency of the obtained composite POE encapsulation film is not improved compared with pure EVA, and it is even reduced to a certain extent.

[0139] Comparative Example 5: Bismuth nitrate and tetraethyl orthosilicate are hydrolyzed to obtain a bismuth-doped silicon oxide precursor, in which bismuth-doped silicon oxide and europium-doped zinc oxide have basically equivalent performance in converting ultraviolet light into visible light. However, the results show that the photoelectric conversion efficiency of the composite EVA encapsulation film obtained by grafting them onto EVA is worse than that of pure EVA.

[0140] Comparative Example 6 shows that when the pH value is not within the range specified in the present invention, the visible light transmittance and photoelectric conversion efficiency of the obtained composite EVA encapsulation film are worse than those of pure EVA.

[0141] Comparative Example 7 shows that the europium doping ratio is higher than that of the present invention, and the visible light transmittance and photoelectric conversion efficiency are also significantly deteriorated.

[0142] Comparative Example 8 shows that the visible light transmittance and photoelectric conversion efficiency of the obtained composite EVA encapsulation film are worse than those of pure EVA when the hydrolysis temperature is lower than that of the present invention.

[0143] Comparative Example 9 shows that the hydrolysis time is shorter than that of the present invention, and the obtained composite EVA encapsulation film is inferior to pure EVA.

[0144] Comparative Example 10 shows that the ratio of the dry mass of the precursor (i.e., the mass of zinc oxide and europium) to the mass of EVA is higher than that of the present invention, and the obtained composite EVA encapsulation film is inferior to that of pure EVA.

Claims

1. A composite EVA material, characterized in that: The invention comprises an EVA matrix, nano ZnO:Eu grafted on the -CO- of the EVA matrix 3+ and free nano ZnO:Eu 3+ ; Total nano ZnO:Eu 3+ The mass percentage of the EVA matrix is ​​not higher than 4.5%, and the total nano ZnO:Eu 3+ Nano ZnO:Eu grafted on the EVA substrate 3+ and the free nano ZnO:Eu 3+ composition; The preparation method of the composite EVA material comprises the following steps: S1: The mixed solution containing zinc source and europium source is hydrolyzed to obtain nano ZnO:Eu 3+ Precursor; the temperature of the hydrolysis reaction is not less than 160°C, and the time of the hydrolysis reaction is not less than 16 hours; the hydrolysis reaction is carried out at a pH of 7 to 10; S2: the nano ZnO:Eu 3+ The precursor and the EVA matrix are subjected to grafting reaction and drying to obtain the composite EVA material; in the composite EVA material, the total nano ZnO:Eu 3+ The mass percentage of the EVA matrix is ​​not higher than 4.5%, and the total nano ZnO:Eu 3+ Nano ZnO:Eu grafted on the EVA 3+ and free nano ZnO:Eu 3+ composition; The total nano ZnO:Eu 3+ The europium doping ratio is 4-10%, wherein the europium doping ratio refers to the mass ratio of europium oxide to zinc oxide.

2. The composite EVA material according to claim 1, characterized in that: It meets one or more of the following conditions: (1) The total nano ZnO:Eu 3+ The mass percentage of the EVA matrix is ​​0.2 to 4%; (2) The EVA matrix is ​​EVA with a vinyl acetate content of 20 to 28%.

3. The composite EVA material according to claim 2, characterized in that: It meets one or more of the following conditions: (1) The total nano ZnO:Eu 3+ In the case of MgO, the doping ratio of europium is 5-8%. (2) The total nano ZnO:Eu 3+ The mass percentage of the EVA matrix is ​​0.5 to 3.5%; (3) The EVA matrix is ​​EVA having a vinyl acetate content of 28%.

4. The composite EVA material according to claim 3, characterized in that: It meets one or both of the following conditions: (1) The total nano ZnO:Eu 3+ The europium doping ratio is 5.56%, 6.10%, 6.35%, 6.42%, 7.14% or 7.67%; (2) The total nano ZnO:Eu 3+ The mass percentage with the EVA matrix is ​​0.53%, 1.06%, 1.61%, 2.10% or 3.50%.

5. The composite EVA material according to claim 2, characterized in that: The total nano ZnO:Eu 3+ The europium doping ratio is 7-8%.

6. A method for preparing a composite EVA material, characterized in that: It includes the following steps: S1: The mixed solution containing zinc source and europium source is hydrolyzed to obtain nano ZnO:Eu 3+ Precursor; the temperature of the hydrolysis reaction is not less than 160°C, and the time of the hydrolysis reaction is not less than 16 hours; the hydrolysis reaction is carried out at a pH of 7 to 10; S2: the nano ZnO:Eu 3+ The precursor and the EVA matrix are subjected to grafting reaction and drying to obtain the composite EVA material; in the composite EVA material, the total nano ZnO:Eu 3+ The mass percentage of the EVA matrix is ​​not higher than 4.5%, and the total nano ZnO:Eu 3+ Nano ZnO:Eu grafted on the EVA 3+ and free nano ZnO:Eu 3+ composition; The total nano ZnO:Eu 3+ The europium doping ratio is 4-10%, wherein the europium doping ratio refers to the mass ratio of europium oxide to zinc oxide.

7. The method for preparing the composite EVA material according to claim 6, characterized in that: It meets one or more of the following conditions: (1) The total nano ZnO:Eu 3+ The mass percentage of the EVA matrix is ​​0.2 to 4%; (2) The EVA matrix is ​​EVA with a vinyl acetate content of 20 to 28%.

8. The method for preparing the composite EVA material according to claim 7, characterized in that: It meets one or more of the following conditions: (1) The total nano ZnO:Eu 3+ In the case of MgO, the doping ratio of europium is 5-8%. (2) The total nano ZnO:Eu 3+ The mass percentage of the EVA matrix is ​​0.5 to 3.5%; (3) The EVA matrix is ​​EVA having a vinyl acetate content of 28%.

9. The method for preparing the composite EVA material according to claim 8, characterized in that: It meets one or both of the following conditions: (1) The total nano ZnO:Eu 3+ The europium doping ratio is 5.56%, 6.10%, 6.35%, 6.42%, 7.14% or 7.67%; (2) The total nano ZnO:Eu 3+ The mass percentage with the EVA matrix is ​​0.53%, 1.06%, 1.61%, 2.10% or 3.50%.

10. The method for preparing the composite EVA material according to claim 7, characterized in that: The total nano ZnO:Eu 3+ The europium doping ratio is 7-8%.

11. The method for preparing a composite EVA material according to any one of claims 6 to 10, characterized in that: It meets one or more of the following conditions: (1) The zinc source is a zinc salt; (2) The europium source is a europium salt; (3) When the zinc source is anhydrous zinc nitrate and the europium source is europium nitrate hexahydrate, the mass ratio of the zinc source to the europium nitrate hexahydrate is 10 to 18; (4) When the zinc source is anhydrous zinc nitrate and the europium source is hexahydrated europium nitrate, the mass ratio of the sum of the mass of the zinc source and the europium source to the mass of the EVA is 0.004 to 0.1; (5) The mixed solution also includes an anionic surfactant; (6) the mixed solution is preheated before the hydrolysis reaction; (7) In step S1, the pH of the hydrolysis reaction is 8.5 to 10; (8) In step S1, the temperature of the hydrolysis reaction is 180-220°C; (9) In step S1, the hydrolysis reaction time is 16 to 30 hours.

12. The method for preparing the composite EVA material according to claim 11, characterized in that: It meets one or more of the following conditions: (1) The zinc source is one or more of zinc nitrate, zinc sulfate and zinc carbonate; (2) The europium source is one or more of europium nitrate, europium sulfate and europium carbonate; (3) When the zinc source is anhydrous zinc nitrate and the europium source is europium nitrate hexahydrate, the mass ratio of the zinc source to the europium nitrate hexahydrate is 12 to 17; (4) When the zinc source is anhydrous zinc nitrate and the europium source is hexahydrated europium nitrate, the mass ratio of the sum of the mass of the zinc source and the europium source to the mass of the EVA is 0.004 to 0.0821; (5) In step S1, the temperature of the hydrolysis reaction is 180°C, 200°C or 220°C; (6) In step S1, the hydrolysis reaction time is 20 to 30 hours.

13. The method for preparing the composite EVA material according to claim 12, characterized in that: It meets one or more of the following conditions: (1) The zinc source is zinc nitrate; (2) The europium source is europium nitrate; (3) when the zinc source is anhydrous zinc nitrate and the europium source is europium nitrate hexahydrate, the mass ratio of the zinc source to the europium nitrate hexahydrate is 12, 12.9, 14.3, 14.5, 15.1 or 16.6; (4) When the zinc source is anhydrous zinc nitrate and the europium source is hexahydrated europium nitrate, the mass ratio of the sum of the mass of the zinc source and the europium source to the mass of the EVA is 0.0046 to 0.0600; (5) In step S1, the hydrolysis reaction time is 20 h, 24 h or 30 h.

14. The method for preparing the composite EVA material according to claim 13, characterized in that: It meets one or both of the following conditions: (1) The europium source is europium nitrate hexahydrate; (2) When the zinc source is anhydrous zinc nitrate and the europium source is hexahydrated europium nitrate, the mass ratio of the sum of the mass of the zinc source and the europium source to the mass of the EVA is 0.0046, 0.0125, 0.0124, 0.0248, 0.0377, 0.0492 or 0.0821.

15. The method for preparing the composite EVA material according to claim 11, characterized in that: The anionic surfactant is sodium dodecylbenzene sulfonate.

16. The method for preparing the composite EVA material according to claim 11, characterized in that: The HLB of the anionic surfactant is 10-15.

17. The method for preparing the composite EVA material according to claim 16, characterized in that: The HLB of the anionic surfactant is 10-12.

18. The method for preparing the composite EVA material according to claim 17, characterized in that: The HLB of the anionic surfactant is 10.

638.

19. The method for preparing the composite EVA material according to claim 11, characterized in that: The mass of the anionic surfactant preferably accounts for 1-6% of the total mass of the zinc source and the europium source.

20. The method for preparing the composite EVA material according to claim 19, characterized in that: The mass of the anionic surfactant preferably accounts for 5-6% of the total mass of the zinc source and the europium source.

21. The method for preparing the composite EVA material according to claim 20, characterized in that: The mass of the anionic surfactant preferably accounts for 5.12%, 5.24%, 5.57%, 5.60%, 5.65% or 5.89% of the total mass of the zinc source and the europium source.

22. The method for preparing the composite EVA material according to claim 11, characterized in that: The preheating temperature is 80-110°C.

23. The method for preparing the composite EVA material according to claim 22, characterized in that: The preheating temperature is 90°C.

24. The method for preparing the composite EVA material according to claim 11, characterized in that: The preheating time is 1-4h.

25. The method for preparing the composite EVA material according to claim 24, characterized in that: The preheating time is 2h.

26. The method for preparing the composite EVA material according to claim 11, characterized in that: In step S1, the pH of the hydrolysis reaction is 8.5, 9.0, 9.5 or 10.

27. The method for preparing the composite EVA material according to claim 11, characterized in that: In step S1, the pH is adjusted with a pH adjuster.

28. The method for preparing the composite EVA material according to claim 27, characterized in that: In step S1, the pH adjuster is an alkaline compound that does not contain metal cations.

29. The method for preparing the composite EVA material according to claim 28, characterized in that: In step S1, the pH adjuster is ammonia water and / or urea.

30. The method for preparing the composite EVA material according to claim 29, characterized in that: In step S1, the pH adjuster is aqueous ammonia.

31. The method for preparing a composite EVA material according to claim 27, wherein: In step S1, the pH adjuster is added dropwise.

32. The method for preparing a composite EVA material according to any one of claims 6 to 10, characterized in that: It meets one or more of the following conditions: (1) In step S2, the EVA is first dissolved in an organic solvent to form an EVA solution, and then mixed with the nano ZnO:Eu 3+ The precursor undergoes the reaction; (2) In step S2, the temperature of the grafting reaction is 80 to 110° C.; (3) In step S2, the grafting reaction time is 1.5 to 3 hours; (4) In step S2, the drying is vacuum drying; (5) In step S2, an extraction step is further included after the grafting reaction and before the drying.

33. The method for preparing the composite EVA material according to claim 32, characterized in that: The organic solvent is toluene.

34. The method for preparing the composite EVA material according to claim 32, characterized in that: The concentration of the EVA solution is 5-15 g / mL.

35. The method for preparing the composite EVA material according to claim 34, characterized in that: The concentration of the EVA solution is 10 g / mL.

36. The method for preparing the composite EVA material according to claim 32, characterized in that: It meets one or more of the following conditions: (1) In step S2, the temperature of the grafting reaction is 90° C.; (2) In step S2, the grafting reaction time is 2 hours; (3) In step S2, the solvent used for the extraction is one or more of toluene, carbon tetrachloride, chloroform and dichloromethane.

37. The method for preparing the composite EVA material according to claim 36, characterized in that: The solvent used for the extraction is toluene.

38. A composite EVA material obtained by the preparation method as described in any one of claims 6-37.

39. A composite EVA packaging film, characterized in that: It is made by molding the composite EVA material as described in any one of claims 1-5 and 38.

40. A composite EVA encapsulation film as claimed in claim 39, characterized in that: The molding method includes internal mixing and stretching molding.

41. A composite EVA encapsulation film as claimed in claim 40, characterized in that: The temperature of the banburying is 90-120°C.

42. A composite EVA encapsulation film as claimed in claim 41, characterized in that: The kneading temperature is 100°C.

43. A composite EVA encapsulation film as claimed in claim 40, characterized in that: The stretching temperature is 120-160°C.

44. A composite EVA encapsulation film as claimed in claim 43, characterized in that: The stretching temperature is 130-150°C.

45. A composite EVA encapsulation film as claimed in claim 44, characterized in that: The stretching temperature was 140°C.

46. ​​A battery cell comprising the composite EVA encapsulation film as claimed in any one of claims 39 to 45.

47. A photovoltaic module, characterized in that: It includes the battery cell as claimed in claim 46.

Citation Information

Patent Citations

  • Nano fluorescent particles doping with rare-earth ions and relevant application thereof

    CN101787272A

  • Preparation method and application of europium-doped zinc oxide photocatalyst

    CN110280234A